LECTURER INNOVATION ON LEARNING MANAGEMENT DURING PANDEMIC TIME AT POSTGRADUATE UIN ALAUDDIN MAKASSAR - Yuliana Yuliana; Sulaiman Saat; Sitti Mania (Universitas Islam Negeri Alauddin Makassar, 2021)
The results of the study stated that the innovation of Postgraduate lecturers at UIN Alauddin Makassar during the pandemic, namely the form of innovation was maximized but the effect or impact of the innovation was not maximized, because it was caused by several factors that were constrained by students, for example network disturbances, when students were making presentations. The innovation of Postgraduate lecturers at UIN Alauddin Makassar in managing learning during the pandemic is less effective because based on the observations of researchers, it shows that some students are constrained in the network when the learning process takes place, students do not follow the lesson well, indicated by the presence of students who do not activate the camera, lack of focus in receive the subject matter, so that it does not achieve the proper learning objectives.